A Health Crisis in the Age of Misinformation: How Social Media and Mass Media Influenced Misperceptions about COVID-19 and Compliance Behavior. Issue 10 (3rd October 2022) - Meppelink, Corine S.; Bos, Linda; Boukes, Mark; Möller, Judith
ABSTRACT: The media are important information disseminators in society. Particularly in uncertain times, such as the COVID-19 pandemic, citizens are very "media dependent." The way in which people are informed about the coronavirus heavily depends on the type of media they use. Especially on social media, the share of misinformation is considerable, which might impact the way in which people comply with preventive measures. Our study investigates how media use affects misperceptions about the coronavirus and whether this influences important behavioral determinants as well as compliance behavior itself. The results of a unique 5-wave panel survey ( N = 1, 741) conducted between April 2020 and October 2020 show that the use of mass media reduces misperceptions. The same was found for Twitter users, whereas Facebook and Instagram users have more misperceptions about the coronavirus. Misperceptions negatively influence the perceived severity, susceptibility and efficacy of preventive measures taken by governments, which may ultimately result in decreased compliance. Our findings underline the important role of media consumption and misperceptions in shaping citizens' beliefs and behavior regarding COVID-19. They re-emphasize the importance of mass media, such as newspapers, television broadcasts or reliable news websites, to inform the public about current affairs. They also imply that platform media might be more heterogeneous in their effects than mass media.